Autonomous precision landing of UAV digital twins on moving platforms and river data analytics from UAV imagery - Ashrafi, Rezwana; Uddin, Jahir; Rafi, Suhail Haque; Raidah, Mashiat Mamun (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.